THE REGULATION OF A PERSON’S RIGHT TO REFUSE TO PERFORM MILITARY SERVICE DUE TO THEIR INTERNAL BELIEFS IN LITHUANIA AND IN THE CONTEXT OF INTERNATIONAL LAW - Tomas Proškus (Jurisprudencija, 2023)
The right of an individual to refuse to perform military service because of their internal beliefs has deep roots in international law. Such a right in the national law of the independent Republic of Lithuania is regulated by the institute of alternative national defense service, which was established in 1996. During the more than two decades in which the alternative national defense service has existed in the national law, this institute has not received particularly significant changes that would correspond to current international law and the legal interpretation of the European Court of Human Rights. Taking this into account, in this study, with the help of international law norms and the legal interpretations in the practice of the European Court of Human Rights, the relationship between the national law norms of the Republic of Lithuania and the interpretation of national court law with the transnational right of a person to refuse to participate in military service due to their internal beliefs is revealed. After conducting this research, it is concluded that the national law of the Republic of Lithuania does not comply with the norms of international law and the practice of interpreting the law formed by the European Court of Human Rights; therefore, it should be adapted by incorporating good international legal practice regarding the right of individuals to refuse to participate in military service due to their internal beliefs.